Analysis of the dynamics of venous blood flow in the context of lower limb temperature distribution and tissue composition in the elderly - Skomudek A (Dove Medical Press, 2017)
Aleksandra Skomudek,1,2 Iwona Gilowska,1,3 Ryszard Jasiński,4 Krystyna Rożek-Piechura4 1Department of Physical Education and Physiotherapy, Opole University of Technology, Opolskie, 2Department of Clinical Physiotherapy, 3Department of Biochemistry and Physiology, 4Department of Physiotherapy and Occupational Therapy in Conservative and Interventional Medicine, University of Physical Education in Wroclaw, Wroclaw, Poland Objective: The elderly are particularly vulnerable to degenerative diseases, such as circulatory and respiratory system and vascular system diseases. The objective of this study was therefore to evaluate the distribution of temperature and the dynamics of venous blood flow in the lower limbs (LLs) and to assess the interdependence of these parameters in terms of the somatic components in males and females participating in activities at the University of the Third Age. Materials and methods: The study included 60 females (mean age 67.4 years) and 40 males (mean age 67.5 years). A body composition assessment was performed using the bioimpedance technique – Tanita BC-418MA. The following parameters were examined: fat%, fat mass, fat-free mass, and total body water. The minimal, maximal, and mean temperature values and their distributions were examined using infrared thermographic camera VarioCAM Head. Measurements of the venous refilling time and the work of the LL venous pump were examined using a Rheo Dopplex II PPG. Results: In males, the mean value of the right LL temperature was 30.58 and the mean value of the left LL was 30.28; the P-value was 0.805769. In females, the mean value of the right LL temperature was 29.58 and the mean value of the left limb was 29.52; the P-value was 0.864773. In males, the right limb blood flow was 34.17 and the left limb blood flow was 34.67; the P-value was 0.359137. In females, the right limb blood flow was 26.89 and the left limb blood flow was 26.09; the P-value was 0.796348. Conclusion: Research results showed that the temperature distribution and the dynamics of blood flow are not significantly different between the right and left extremities in both males and females. However, significant temperature differences were found between the gender groups. Significantly higher temperature values in both the right and left extremities were recorded in males than in females. Keywords: thermovision, lower limb, blood circulation